Rural–urban and socio-demographic diferentials in perceived health state among aging population in Ghana - Yawson, A.E.; Boateng, R.; Adoma, P.O. (Journal of Health, Population and Nutrition, 2023)
Background The variations in health between rural and urban population have become an increasingly signifcant public health concern in developing countries including Ghana where urbanization is occurring. Whereas urbanization results in improved access to healthcare services, the concomitant negative consequences of urbanization coupled with unfavorable compositional and contextual attributes can afect the health of populations. The study sought to examine the efect of rural–urban residence and selected socio-demographic factors on perceived health state among aging population by employing a nationally representative data collected by the WHO from 2014 to 2015. Methods The data were derived from the WHO Study on Aging wave 2 released in 2019. A total of 4511 individuals, made up of 1018 adults between 18 and 49 years and 3493 respondents within the ages of 50 years and above, were involved in this study. The study examined the Spearman’s rho correlations between perceived health, rural–urban residence, age, sex, marital status, ever schooled, current work state, religion, and regional location. Subsequently, the study employed a multivariable ordinal logistic regression model to test the efect of the selected biosocial and contextual variables on perceived health state. Results The selected socio-demographic variables signifcantly correlated with health state, except for rural–urban residence. However, the predictive ability of rural–urban residence and the socio-demographic variables on perceived health state were strongly ascertained. It was observed that age, sex, rural–urban residence, and current state of work among aging populations were signifcant predictors of perceived health state as demonstrated by odds ratios and signifcant p values. The contextual factor of regional location was the most signifcant variable that increases the perceived health state of respondents in the study. Conclusions Continues engagement in work-related activities, an individual’s age within the aging continuum and regional location coupled with its environmental and ecological attributes, may signifcantly infuence the development of positive perception toward health state, which forms a vital constituent of an individual health seeking behavior.
Reserach Articles
Keywords: Aging population; Perceived health state; SAGE 2; Ghana; Vulnerability diferentials